Fiber-reinforced high-entropy alloy and preparation method thereof

By adding an appropriate amount of carbon fiber to the high-entropy alloy and using high-entropy ball mill and discharge plasma sintering technology to prepare fiber-reinforced high-entropy alloys, the problem of improving the performance of high-entropy alloys is solved and the strength and performance is significantly improved.

CN119753532APending Publication Date: 2025-04-04YANSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510037368.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

There is a need in the prior art to improve and optimize the performance of high entropy alloys, especially by utilizing carbon fibers to enhance the performance of high entropy alloys.

Method used

The fiber-reinforced high-entropy alloy was prepared by a high-entropy alloy CoCrNiCuFe mass fraction of 50 to 70 wt.%, the carbon fiber Cf mass fraction of 0.1 to 0.9 wt.%, and the residual solid lubricating phase. The fiber-reinforced high-entropy alloy was prepared by a high-energy ball mill and discharge plasma sintering technology.

Benefits of technology

The addition of carbon fiber makes it embedded in the grains of high-entropy alloys, hindering dislocation movement and grain growth, thereby improving the strength and overall performance of high-entropy alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753532A_ABST
    Figure CN119753532A_ABST
Patent Text Reader

Abstract

The invention discloses a fiber-reinforced high-entropy alloy and a preparation method thereof. The fiber-reinforced high-entropy alloy is characterized by comprising the following components in percentage by mass: 50-70% of high-entropy alloy CoCrNiCuFe, 0.1-0.9% of carbon fiber Cf and the balance of solid lubricating phase. According to the method, the carbon fibers are completely embedded into high-entropy alloy crystal grains, dislocation movement of the high-entropy alloy and growth of the crystal grains are hindered, and therefore the strength of the high-entropy alloy is improved. The carbon fibers can pinning grain boundaries, hinder dislocation motion and improve dislocation density, so that the material is strengthened, and the carbon fibers improve the overall performance of the high-entropy alloy well.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal matrix composite materials, and in particular, relates to a fiber reinforced high entropy alloy and a preparation method thereof. Background Art

[0002] Since its birth, high entropy alloys have shown excellent mechanical properties, good corrosion resistance, thermal stability, wear resistance, etc., and have a very broad development space. Studies have found that the equiatomic ratio CoCrNiCuFe high entropy alloy with a face-centered cubic (FCC) phase structure has good strain hardening properties, and can produce extremely high tensile elongation and excellent fracture toughness even at low temperatures. It is a good choice to replace steel in some fields, such as high-speed cutting tools, mold materials, chemical materials, ship materials, and electric heating materials. Although pure high entropy alloy solid solutions have shown their good performance, their versatility still has its shortcomings. Studies have found that high entropy alloys have the characteristics of severe lattice distortion and slow diffusion behavior, and the performance and application of high entropy alloys can be further improved by introducing interstitial atoms. The effect of element doping on the performance of high entropy alloys is very significant. According to the different types of added elements, the performance orientation of high entropy alloys will also have differentiated choices. For example, elements such as Mn, Cr, Ni, Al, Ti, Mo, C, and Si can play a good strengthening role. The addition of strengthening phase is also an excellent strengthening solution, which can directly introduce some unique properties, such as the strength of TiB2, TiC, wear resistance and corrosion resistance of Al2O3, unique properties of graphene, carbon fiber, etc. Therefore, high entropy alloys have rapidly developed into an important metal material resource in recent years and have been widely studied and applied.

[0003] C is a small-sized light element that exists in various forms, such as graphite, diamond, carbon fiber, graphene, and even most carbides. Therefore, there have been many studies on the strengthening and toughening mechanism of C. As a strengthening phase particle, C can be used for solid solution strengthening, fine grain strengthening, precipitation strengthening and other strengthening methods. It is an important element for exploring the strengthening and toughening of composite materials. C can form carbide precipitation with elements in high entropy alloys, which enhances the solid solution strengthening effect and improves the overall performance. C can also reduce the stacking fault energy of high entropy alloys, form more slip bands, and improve their ductility. At present, how to use carbon fiber to enhance the performance of high entropy alloys is an urgent problem to be solved. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a fiber-reinforced high-entropy alloy and a preparation method thereof, which solves the problem in the prior art of needing to improve and optimize the performance of high-entropy alloys.

[0005] In order to solve the above technical problems, the present invention discloses a fiber-reinforced high entropy alloy, characterized in that the mass fraction of the high entropy alloy CoCrNiCuFe is 50-70wt.%, the mass fraction of the carbon fiber Cf is 0.1-0.9wt.%, and the balance is a solid lubricating phase.

[0006] A method for preparing a fiber-reinforced high entropy alloy, characterized in that it comprises the following steps: S1, preparation of CoCrNiCuFe high entropy alloy powder; S2, preparation of a high entropy alloy composite material sintered body; wherein: S1. Preparation of CoCrNiCuFe high entropy alloy powder: A high energy ball mill (GN-2) was provided. The ball mill was a steel mill. Three sizes of steel balls with diameters of 10 mm, 8 mm, and 6 mm were used. The mass ratio of large, medium, and small balls was 6:3:1, and the ball-to-material ratio was 10:1. The mass of steel balls loaded into a single mill was 100 g, and the mass of the mixed powder was 10 g. According to the high entropy alloy synthesis standard, 2.039 g Co, 1.799 g Cr, 2.031 g Ni, 2.199 g Cu, and 1.932 g Fe were weighed in an argon-filled glove box in equal molar ratios and placed in a steel ball mill with a volume of 250 ml. 0.4 ml of anhydrous ethanol was added as a dispersant. The ball mill was sealed and then placed on a high energy ball mill (GN-2, China) for ball milling. The ball mill speed was set to 350 r / min, the ball milling time was 30 h, and the ball mill was stopped for 2 seconds after every 5 h of rotation. h for heat dissipation, and the machine was stopped every 10 h to scrape off the raw materials adhering to the grinding balls and the inner wall of the tank in an argon atmosphere glove box and mix them evenly, and then 0.3 ml of anhydrous ethanol was added to each tank to continue ball milling to obtain CoCrNiCuFe high entropy alloy powder; S2. Preparation of high entropy alloy composite sintered body: the experimentally prepared CoCrNiCuFe high entropy alloy powder is added to carbon fiber in proportion, mixed by a high-energy ball mill, and prepared into a composite block by spark plasma sintering.

[0007] Furthermore, in the above step S2, in an argon atmosphere in a glove box, 5 g of a certain proportion of mixed powder is placed in a high-energy ball mill, the ball-to-material ratio is 10:1, the diameters of the steel balls are 10 mm, 8 mm, and 6 mm, respectively, the number ratio is 6:3:1, the rotation speed is 200 r / min, 0.2 ml of anhydrous ethanol dispersant is added, and the mixture is blended for 2 h; the ball-milled powder is sieved in the glove box, 3 to 5 g of the composite powder is weighed with an electronic balance and loaded into a graphite mold, the inner wall of the graphite mold is wrapped with 32.5 mm×45 mm×0.2 mm graphite paper, and the assembled mold is pre-pressed and pre-pressed at 30 MPa for 30 s.

[0008] Furthermore, in the above step S2, a spark plasma sintering test machine (LABOXTM-110 model) is used to prepare a high entropy alloy block, and a graphite mold is placed in an SPS sintering machine and axially pressurized to 30-50 MPa, and sintering is started when the SPS vacuum is lower than 100 Pa. Infrared temperature measurement is used for sintering, and the temperature is heated from room temperature to 600 ° C within 5 minutes, and kept at 600 ° C for 10 minutes. After the insulation is completed, the vacuum button is closed, the argon valve is opened, and argon is filled to -0.05 Pa; then the temperature is increased to a temperature close to the target temperature at a heating rate of 50-100 ° C / min, and then the target temperature is reached through a slow heating mechanism, and the temperature is kept for 5-15 minutes; after the insulation is completed, the mold and the SPS sintering machine are cooled to below 60 ° C, the pressure is released and the hatch is opened, and the mold is disassembled to obtain a sintered block, and the surface of the sintered block is polished and polished to obtain a high entropy alloy block.

[0009] Furthermore, the particle size of the high entropy alloy is less than 150 nm; the purity of the carbon fiber Cf is greater than 99%, and the particle size is less than 150 nm.

[0010] Furthermore, the purity of the high entropy alloy powder is greater than 99%, wherein the particle size of the Co powder is 1 to 3 μm, the particle size of the Ni powder is 3 to 5 μm, and the particle size of the remaining metal element powders is less than 30 μm.

[0011] Compared with the prior art, the present application can obtain the following technical effects: The present invention allows the addition of carbon fibers to be more completely embedded in the high entropy alloy grains, hindering the movement of dislocations and grain growth of the high entropy alloy, thereby improving the strength of the high entropy alloy. Carbon fibers can pin the grain boundaries, hinder the movement of dislocations, increase the dislocation density, and thus strengthen the material. Carbon fibers have a good effect on improving the overall performance of the high entropy alloy.

[0012] Of course, any product implementing this application does not necessarily need to achieve all of the technical effects described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 is the XRD pattern of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite; Figure 2 It is the SEM image and EDS point analysis image of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite material; Figure 3It is the SEM image and EDS surface analysis image of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite material; Figure 4 It is the SEM and EDS point analysis diagram of the fracture of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite material; Figure 5 It is the SEM and EDS surface analysis of the fracture of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite material; Figure 6 It is the stress-strain curve of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite. DETAILED DESCRIPTION

[0014] The following will describe the implementation methods of the present application in detail with the help of accompanying drawings and examples, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0015] The invention discloses a fiber-reinforced high-entropy alloy. The mass fraction of the high-entropy alloy CoCrNiCuFe is 50-70wt.%, the mass fraction of the carbon fiber Cf is 0.1-0.9wt.%, and the balance is a solid lubricating phase.

[0016] The present invention also discloses a method for preparing a fiber-reinforced high entropy alloy, which is characterized by comprising the following steps: S1, preparation of CoCrNiCuFe high entropy alloy powder; S2, preparation of a high entropy alloy composite material sintered body; wherein: S1. Preparation of CoCrNiCuFe high entropy alloy powder: A high energy ball mill (GN-2) was provided. The ball mill was a steel mill. Three sizes of steel balls with diameters of 10 mm, 8 mm, and 6 mm were used. The mass ratio of large, medium, and small balls was 6:3:1, and the ball-to-material ratio was 10:1. The mass of steel balls loaded into a single mill was 100 g, and the mass of the mixed powder was 10 g. According to the high entropy alloy synthesis standard, 2.039 g Co, 1.799 g Cr, 2.031 g Ni, 2.199 g Cu, and 1.932 g Fe were weighed in an argon-filled glove box in equal molar ratios and placed in a steel ball mill with a volume of 250 ml. 0.4 ml of anhydrous ethanol was added as a dispersant. The ball mill was sealed and then placed on a high energy ball mill (GN-2, China) for ball milling. The ball mill speed was set to 350 r / min, the ball milling time was 30 h, and the ball mill was stopped for 2 seconds after every 5 h of rotation. h for heat dissipation, and the machine was stopped every 10 h to scrape off the raw materials adhering to the grinding balls and the inner wall of the tank in an argon atmosphere glove box and mix them evenly, and then 0.3 ml of anhydrous ethanol was added to each tank to continue ball milling to obtain CoCrNiCuFe high entropy alloy powder; Preparation of S2 high entropy alloy composite sintered body, the experimentally prepared CoCrNiCuFe high entropy alloy powder was added to carbon fiber in proportion, and mixed using a high-energy ball mill, and spark plasma sintering was used to prepare a composite block.

[0017] According to one embodiment of the present invention, in step S2, in an argon atmosphere in a glove box, 5 g of a certain proportion of mixed powder is placed in a high-energy ball mill, the ball-to-material ratio is 10:1, the diameters of the steel balls are 10 mm, 8 mm, and 6 mm, respectively, the number ratio is 6:3:1, the rotation speed is 200 r / min, 0.2 ml of anhydrous ethanol dispersant is added, and the mixture is blended for 2 h; the ball-milled powder is sieved in the glove box, 3-5 g of the composite powder is weighed with an electronic balance and loaded into a graphite mold, the inner wall of the graphite mold is coated with 32.5 mm×45 mm×0.2 mm graphite paper, the assembled mold is pre-pressed, and pre-pressed for 30 s at 30 MPa.

[0018] According to one embodiment of the present invention, in step S2, a spark plasma sintering test machine (LABOXTM-110 type) is used to prepare a high entropy alloy block, and a graphite mold is placed in an SPS sintering machine and axially pressurized to 30-50 MPa, and sintering is started when the SPS vacuum is lower than 100 Pa. Infrared temperature measurement is used for sintering, and the temperature is heated from room temperature to 600 ° C within 5 min, and kept at 600 ° C for 10 min. After the insulation is completed, the vacuum button is closed, the argon valve is opened, and argon is filled to -0.05 Pa; then the temperature is raised to a temperature close to the target temperature at a heating rate of 50-100 ° C / min, and then the target temperature is reached by a slow heating mechanism, and the temperature is kept for 5-15 minutes; after the insulation is completed, the mold and the SPS sintering machine are cooled to below 60 ° C, the pressure is released and the hatch is opened, and the mold is disassembled to obtain a sintered block, and the surface of the sintered block is polished and polished to obtain a high entropy alloy block.

[0019] According to one embodiment of the present invention, the particle size of the high entropy alloy is less than 150 nm; the purity of the carbon fiber Cf is greater than 99%, and the particle size is less than 150 nm.

[0020] According to one embodiment of the present invention, the purity of the high entropy alloy powder is >99%, wherein the particle size of the Co powder is 1-3 μm, the particle size of the Ni powder is 3-5 μm, and the particle size of the remaining metal element powders is <30 μm.

[0021] Figure 1This is the XRD diagram of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite material. It can be seen that the composite material forms a single-phase solid solution with a trace amount of impurity phase. The phase analysis using jade software found that the lattice constant is 3.615 Å, the grain size is about 205.8 nm, and there are Co, Fe, Cr carbides and insoluble C in the composite material.

[0022] Figure 2 The following are the SEM images and EDS point analysis images of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composites. Figures (a), (b), (c), and (d) are 3000, 5000, 10000, and 20000 times magnification, respectively. Table 1 is the EDS point analysis results of each point area in Figure (c). It can be seen that the different shades of organization in Figure (a) are evenly distributed. Combined with the organization analysis of graphite-enhanced high entropy alloys, it can be seen that this is because the uneven distribution of Cr elements leads to the appearance of Cr-rich and Cr-poor areas. By gradually enlarging the local area, it can be seen that there is no obvious special organization on the surface of the composite material except for several scattered black areas. Comparing the SEM images of CoCrNiCuFe and 0.15 wt.% C-CoCrNiCuFe, it is found that the morphology of the composite material is closer to the matrix morphology, and the organization morphology of 0.15 wt.% C-CoCrNiCuFe is finer, indicating that the fine grain strengthening effect of graphite is better. EDS point analysis of Figure (c) shows that the C content in point 1 is significantly higher than that in other areas, and this area is considered to be a C aggregation area. The element composition content of each point area is slightly different, mainly because the distribution trend of Cr is quite different from that of other elements, which is consistent with the morphology and organization. In addition, except for area 1, the Cr and C content show a correlation, which is due to the generation of Cr3C2.

[0023]

[0024] Figure 3 This is the SEM image and EDS surface analysis image of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite material. Combined with XRD phase analysis, the morphology of the composite material was observed and EDS surface analysis was performed. It was found that the distribution of each element component was relatively uniform. Comparing the morphology before and after the addition of carbon fiber, it was found that the carbon fiber had little effect on the structure of the CoCrNiCuFe high entropy alloy. It can be seen that the C content in area A in the figure is relatively high. This is the C aggregation area, and the carbon fiber structure is not very obvious.

[0025]

[0026] Combined with the EDS surface analysis results in Table 2, it is found that the atomic percentages of Co, Cr, Ni, Cu, and Fe are close to 1:1:1:1:1, indicating that the addition of carbon fiber will not destroy the original organizational structure of the high entropy alloy, but compared with the addition of graphite, carbon fiber can be observed on the surface of the material, indicating that the role of carbon fiber in CoCrNiCuFe is different from that of graphite. When carbon fiber enters the high entropy alloy, it will be distributed in the grains and grain boundaries, causing a small part of the crystal, hindering the movement of dislocations and grain growth, and increasing the dislocation density; and according to previous experiments, the addition of graphite will enter the lattice gaps and grain boundaries of the high entropy alloy, resulting in solid solution strengthening and fine grain strengthening.

[0027] Figure 4 This is the SEM image of the fracture of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite material. Figure 5 Table 3 is the EDS point and surface analysis diagram of the fracture of 0.15 wt.% Cf-CoCrNiCuFe high entropy alloy composite material. Figure 4 EDS surface analysis results. The fracture scanning can more completely and clearly observe the organizational position of the carbon fiber, which is embedded in the high entropy alloy matrix. Combined with the plane scanning, it is found that the O element is less distributed near the carbon fiber organization, and the carbon fiber can inhibit the oxidation of the surrounding metal. The distribution of metal elements in the fracture and plane is similar, and the molar ratio is close. The content of Cr and Fe elements that have better bonding with C is slightly higher. From Figure 4 It can be seen that the carbon fiber has a good bond with the matrix, there is no element diffusion, and there is no gap or shedding at the joint.

[0028] Table 4 is Figure 5 EDS point analysis results of the SEM image. The C content in the point 1 area is very high; the O content in the point 2 area is very low, and the oxidation of the metal is suppressed due to the effect of carbon fiber; the points 3 and 4 areas are high-entropy alloy matrices, with low C content, increased O content, and metal elements close to an equimolar ratio.

[0029]

[0030] Figure 6This is the stress-strain curve of 0.15 wt.%Cf-CoCrNiCuFe high entropy alloy composite. Compared with 0.15wt.%C-CoCrNiCuFe high entropy alloy composite, the density and compactness of 0.15 wt.%Cf-CoCrNiCuFe high entropy alloy composite do not change much, and the hardness decreases slightly, but it has a significant improvement compared with the matrix. This is because the structures and properties of the two strengthening particles are different, and the strengthening methods are also different. It also shows that solid solution strengthening and fine grain strengthening have better strengthening effects on high entropy alloys. The yield strength of the two materials is similar, but the compressive strength of 0.15 wt.%Cf-CoCrNiCuFe high entropy alloy composite is higher. This is because the size of carbon fiber is larger, and it plays a greater role when the material is subjected to overall force, which can hinder the movement of grain boundaries and improve strength.

[0031]

[0032] In summary, the addition of carbon fiber is more completely embedded in the high entropy alloy grains, which hinders the movement of dislocations and grain growth of high entropy alloys, thereby improving the strength of high entropy alloys. Carbon fiber can pin the grain boundaries, hinder dislocation movement, increase dislocation density, and thus strengthen the material. Carbon fiber has a good improvement on the overall performance of high entropy alloys.

[0033] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and variations made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A fiber-reinforced high entropy alloy, characterized in that: The mass fraction of the high entropy alloy CoCrNiCuFe is 50-70wt.%, the mass fraction of the carbon fiber Cf is 0.1-0.9wt.%, and the balance is a solid lubricating phase.

2. A method for preparing the fiber-reinforced high entropy alloy as claimed in claim 1, characterized in that: The following steps are involved: S1. Preparation of CoCrNiCuFe high entropy alloy powder; S2. Preparation of high entropy alloy composite sintered body; wherein: S1. Preparation of CoCrNiCuFe high entropy alloy powder: A high energy ball mill (GN-2) was provided. The ball mill was a steel can. Three sizes of steel balls with diameters of 10 mm, 8 mm, and 6 mm were used. The mass ratio of large, medium, and small balls was 6:3:1, and the ball-to-material ratio was 10:

1. The mass of steel balls loaded into a single can was 100 g, and the mass of the mixed powder was 10 g. According to the high entropy alloy synthesis standard, 2.039 g Co, 1.799 g Cr, 2.031 g Ni, 2.199 g Cu, and 1.932 g Fe were weighed in an argon-filled glove box in equal molar ratios and placed in a steel ball mill with a volume of 250 ml. 0.4 ml of anhydrous ethanol was added as a dispersant. The ball mill was sealed and then placed on a high energy ball mill (GN-2, China) for ball milling. The ball mill speed was set to 350 r / min, the ball milling time was 30 h, and the ball mill was stopped for 2 min every 5 h. h for heat dissipation, and the machine was stopped every 10 h to scrape off the raw materials adhering to the grinding balls and the inner wall of the tank in an argon atmosphere glove box and mix them evenly, and then 0.3 ml of anhydrous ethanol was added to each tank to continue ball milling to obtain CoCrNiCuFe high entropy alloy powder; S2. Preparation of high entropy alloy composite sintered body: the experimentally prepared CoCrNiCuFe high entropy alloy powder is added to carbon fiber in proportion, mixed by a high-energy ball mill, and prepared into a composite block by spark plasma sintering.

3. The method for preparing a fiber-reinforced high entropy alloy according to claim 2, characterized in that: Wherein, in step S2, in an argon atmosphere of a glove box, 5 g of a certain proportion of mixed powder is placed in a high-energy ball mill, with a ball-to-material ratio of 10:1, wherein the diameters of the steel balls are 10 mm, 8 mm, and 6 mm, respectively, and the number ratio is 6:3:1, the rotation speed is 200 r / min, 0.2 ml of anhydrous ethanol dispersant is added, and the mixture is blended for 2 h; the ball-milled powder is sieved in the glove box, 3 to 5 g of the composite powder is weighed with an electronic balance and loaded into a graphite mold, the inner wall of the graphite mold is wrapped with 32.5 mm×45 mm×0.2 mm graphite paper, and the assembled mold is pre-pressed and pre-pressed at 30 MPa for 30 s.

4. The method for preparing a fiber-reinforced high entropy alloy according to claim 2, characterized in that: In step S2, a spark plasma sintering test machine (LABOXTM-110) is used to prepare a high entropy alloy block, and a graphite mold is placed in an SPS sintering machine and axially pressurized to 30-50 MPa. Sintering is started when the SPS vacuum is lower than 100 Pa. Infrared temperature measurement is used for sintering, and the temperature is heated from room temperature to 600 °C within 5 min, and kept at 600 °C for 10 min. After the insulation is completed, the vacuum button is closed, the argon valve is opened, and argon is filled to -0.05 Pa; then the temperature is raised to a temperature close to the target temperature at a heating rate of 50-100 °C / min, and then the target temperature is reached through a slow heating mechanism, and the temperature is kept for 5-15 min; After the insulation is completed, the mold and the SPS sintering machine are cooled to below 60 °C, the pressure is released and the hatch is opened. The mold is disassembled to obtain a sintered block, and the surface of the sintered block is polished to finally obtain a high entropy alloy block.

5. The method for preparing a fiber-reinforced high entropy alloy according to claim 2, characterized in that: The particle size of the high entropy alloy is less than 150 nm; the purity of the carbon fiber Cf is greater than 99%, and the particle size is less than 150 nm.

6. The method for preparing a fiber-reinforced high entropy alloy according to claim 2, characterized in that: The purity of the high entropy alloy powder is greater than 99%, wherein the particle size of the Co powder is 1 to 3 μm, the particle size of the Ni powder is 3 to 5 μm, and the particle size of the remaining metal element powders is less than 30 μm.